Identifying and exploring biohydrogenating rumen bacteria with emphasis on pathways including trans-10 intermediates - Lore Dewanckele; Jeyamalar Jeyanathan; Bruno Vlaeminck; Veerle Fievez (BMC Microbiology, 2020)
Abstract Background Bacteria involved in ruminal formation of trans-10 intermediates are unclear. Therefore, this study aimed at identifying rumen bacteria that produce trans-10 intermediates from 18-carbon unsaturated fatty acids. Results Pure cultures of 28 rumen bacterial species were incubated individually in the presence of 40 μg/mL 18:3n-3, 18:2n-6 or trans-11 18:1 under control or lactate-enriched (200 mM Na lactate) conditions for 24 h. Of the 28 strains, Cutibacterium acnes (formerly Propionibacterium acnes) was the only bacterium found to produce trans-10 intermediates from 18:3n-3 and 18:2n-6, irrespective of the growth condition. To further assess the potential importance of this species in the trans-11 to trans-10 shift, different biomass ratios of Butyrivibrio fibrisolvens (as a trans-11 producer) and C. acnes were incubated in different growth media (control, low pH and 22:6n-3 enriched media) containing 40 μg/mL 18:2n-6. Under control conditions, a trans-10 shift, defined in the current study as trans-10/trans-11 ≥ 0.9, occurred when the biomass of C. acnes represented between 90 and 98% of the inoculum. A low pH or addition of 22:6n-3 inhibited cis-9, trans-11 CLA and trans-10, cis-12 CLA formation by B. fibrisolvens and C. acnes, respectively, whereby C. acnes seemed to be more tolerant. This resulted in a decreased biomass of C. acnes required at inoculation to induce a trans-10 shift to 50% (low pH) and 90% (22:6n-3 addition). Conclusions Among the bacterial species studied, C. acnes was the only bacterium that have the metabolic ability to produce trans-10 intermediates from 18:3n-3 and 18:2n-6. Nevertheless, this experiment revealed that it is unlikely that C. acnes is the only or predominant species involved in the trans-11 to trans-10 shift in vivo.